Opowiadania oświęcimskie – opowieść edytorska - Tramer, Maciej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
Opowiadania oświęcimskie (Auschwitz stories) by Maria Zarębińska-Broniewska were first published in a book version in 1948. All the texts included in the book, however, had been written earlier. The first ones were first released in a daily newspaper „Polska Zbrojna” („Armed Poland”) in early June 1945, just a few days after the author’s return from a concentration camp. They were one of the first accounts which concerned women concentration camps. The book which was published later included nine out of eleven short stories written by Zarębińska. The manuscript of the synopsis of the book was also saved. However, a very ambitious project of creating tens of short stories was not completed due to the author’s death. This article is a description of individual editions of Auschwitz stories in the years 1948, 1960 and 1971, which become better in form, but move away from the original project which was hidden in the handwritten notes.